ADAPTING RECIPROCAL TEACHING STRATEGY TO IMPROVE EFL STUDENTS’ READING COMPREHENSION: A CASE STUDY AT JUNIOR SECONDARY LEVEL - Hani Fitriyah Nur'aini; Yuna Tresna Wahyuna; Nina Puspitaloka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the implementation of the Reciprocal Teaching Strategy (RTS) to enhance reading comprehension among EFL students at the junior secondary level. Reciprocal Teaching Strategy incorporates four main strategies—predicting, questioning, clarifying, and summarizing—to promote metacognitive awareness and collaborative learning. Employing a qualitative case study design, this research was conducted at a public junior high school in Karawang, Indonesia. Data were collected through classroom observation, semi-structured interviews with one English teacher and three students, and documentation analysis. The findings reveal that Reciprocal Teaching Strategy was implemented through guided modeling, group roles, and repeated practice, resulting in improved student participation and comprehension, especially during predicting and clarifying activities. However, challenges emerged, including students’ unfamiliarity with reflective strategies, varied proficiency levels, and limited classroom resources. Despite these obstacles, the teacher’s adaptive approach contributed significantly to the effectiveness of Reciprocal Teaching Strategy. This study highlights the importance of strategic scaffolding and role assignment in EFL reading instruction. It also provides insights for practitioners seeking to apply Reciprocal Teaching Strategy in similar contexts.